Fabrication of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) biocomposites with reinforcement by hydroxyapatite using extrusion processing - Oner, Mualla; Ilhan, Berna (ELSEVIER, 2016)
The aim of this study was to prepare poly(3-hydroxybutyrate-co-3-hydroxyvalerate), PHBV, biocomposites with incorporating various percentages of hydroxyapatite (HAP) using extrusion processing. The biocomposites were produced by melt extrusion of PHBV with untreated HAP and surface-treated HAP crystals. The structure of bio-polymer/HAP biocomposites was investigated by XRD, FrIR, DSC and SEM. Silane coupling agent was used for HAP surface treatment in PHBV/HAP composites. Silane-treated HAP nanoparticles yielded nanocomposites characterized by good mechanical performance and fine nanofiller dispersion, as shown by SEM investigations. The Halpin-Tsai and Hui-Shia models were used to evaluate the effect of reinforcement by HAP particles on the elastic modulus of the composites. Micromechanical models for initial composite stiffness showed good correlation with experimental values. Disparities in the Halpin-Tsai model were evident for composite with higher HAP loadings. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Bionanocomposite; Mechanical properties; Thermal properties; Poly(3-hydroxybutyrate-co-3-hydroxyvalerate); MECHANICAL-PROPERTIES; BARRIER PROPERTIES; THERMAL-PROPERTIES; FIBER COMPOSITES; POLY(3-HYDROXYBUTYRATE); POLYHYDROXYALKANOATES; POLYHYDROXYBUTYRATE; CRYSTALLIZATION; NANOCOMPOSITES; MORPHOLOGY; Materials Science